Hope anchored in practice - Dreyer, LM (South African Journal of Higher Education, 2011)
In South Africa, the processes of democratisation and social restructuring are inextricably linked to the debate on inclusive education. Although the debate on inclusive education originated in the disability discourse, it is increasingly viewed broader as a reform that supports and welcomes diversity. While the constitution and policy framework in the new South Africa is internationally recognised as of the most progressive regarding human rights, research shows great concerns regarding the gap between policy and implementation thereof. From a human rights and social justice perspective, education is viewed as a basic human right and the foundation for a more just and equal society. In this article I will therefore draw on Paulo Freire’s (1998) notion of ‘pedagogy of hope’ and root my argument in his definition that hope is ‘an ontological need that should be anchored in practice in order to become historical concreteness’.